Characterizing Preceptor Effectiveness in Student-Run Free Clinics: Perspectives of Current Students and Preceptors - Rashika Shetty; Briana Clifton; Aanish Puri; Molly Weavers; Patrick Acton; Brian Sick (Journal of Student-Run Clinics, 2025)
Background: Phillips Neighborhood Clinic (PNC) is an interprofessional, student-run free clinic in Minneapolis, Minnesota that serves underrepresented and underinsured patients. Preceptors play a critical but inconsistently defined role at PNC, with no formal training on feedback deliver or diversity, equity, and inclusion (DEI) practices. This project sought to understand and address the training needs for preceptors.Methods: One 32-question survey was emailed to preceptors, and another 12-question survey was sent to student volunteers. Quantitative analysis included Mann-Whitney U test was used to compare preceptors with and without PNC training and those with and without experience precepting students. Student perception was also measured with correlational analysis (p<0.05). Quantitative analysis involved identifying key themes for preceptor training and improvement.Results: In total, 29 preceptors (25.9%) and 43 students (10.6%) completed the surveys. Twenty-three preceptors (79.3%) reported having worked with students outside of PNC, and 25 (86.2%) had received prior DEI training. Only 17 preceptors (58.6%) reported receiving training for their preceptor role at PNC. Analysis of responses showed a statistically significant difference in preceptor comfortability in their role between those who did and did not receive PNC training. Analysis of survey responses showed no statistically significant difference in providing feedback between preceptors who work with students outside of PNC and those who do not. Through thematic analysis students were found to report that preceptors lacked information on several DEI topics. Students also reported receiving inconsistent frequency and types of feedback from their preceptors. Preceptors did not identify either of these as major concerns within their survey.Conclusions: The results identified not only a difference between preceptors who received PNC training, but also different perspectives between preceptors and students regarding preceptor roles and effectiveness. These findings will inform future formal preceptor competency training programs and a standardized method for providing and receiving feedback.